A companion to Latin Greece
1 online resource.
Keywords: The conquest of the Byzantine Empire by the armies of the Fourth Crusade resulted in the foundation of several Latin political entities in the lands of Greece. The Companion to Latin Greece offers thematic overviews of the history of the mixed societies that emerged as a result of the conquest. With dedicated chapters on the art, literature, architecture, numismatics, economy, social and religious organisation and the crusading involvement of these Latin states, the volume offers an introduction to the study of Latin Greece and a sampler of the directions in which the field of research is moving. Contributors are: Nikolaos Chrissis, Charalambos Gasparis, Anastasia Papadia-Lala, Nicholas Coureas, David Jaccoby, Julian Baker, Gill Page, Maria Georgopoulou and Sophia Kalopissi-Verti.